Women’s entrepreneurship – a promising potential for economic development - Akybayeva, G.S.; Mussabekova, A.O.; Pechkovskaya, V.V.; Starikova, T.V.; Davletbayeva, N.B. (BUKETOV BUSINESS REVIEW, 2023)
Object: The article describes the trends in the development of women's entrepreneurship in the second half of the 19th century and in the early 20th century, which are established on the basis of statistical materials, measures taken by the country's leadership, and facts of interest to readers. Ways of overcoming the identified barriers are suggested to enable women to realize their ideas and benefit the society. Methods: When writing the article, a general scientific methodology was used to analyze the theoretical and practical materials on the development of women's entrepreneurship. Based on the assessment of the development of women's business in the historical aspect and comparative analysis, as well as using a systematic approach, an assessment is made of the role of women's entrepreneurship in the economy of Kazakhstan. Findings: The active development of the social group of business women with equal participation in the market contributes to the effective promotion of a number of socio-economic and political tasks of the state and creates favorable conditions for the economic growth of the country's economy. Conclusions: Statistical materials show that the development of women's business in the subsequent period was notable for its intensity regardless of objective and subjective reasons that created difficulties for female entrepreneurs. The entrepreneurial potential of women can significantly contribute to the implementation of new priority projects of socio-economic development. The article written within the framework of the project: Grant No. AP14871920.